User Needs in Sustainable Reporting: The views of Non-Governmental Organizations in Malaysia - Loke, Eu Kong (2006)
The renaissance of practitioner and academician on engagement with sustainable reporting (SR) continue strongly into the 21st century (Elkington, 2001; Ernst and Young, 2002; Logsdon and Lewellyn, 2000). In recent years, we have seen increasing pressure from many sectors of society for companies to be more accountable for their social and environmental impact. Some attribute these changes to shifts in the way people think, whilst others concluded that there are now genuine concerns on the balance in sharing the responsibilities and accountabilities towards the welfare of society and the well being of the surrounding in general.